2016
DOI: 10.1186/s12879-016-1399-0
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Acinetobacter baumannii in an intensive care unit in the Western part of Romania

Abstract: BackgroundAcinetobacter baumannii is one of the main causes of morbidity and mortality in critical condition patients. The pathogen’s ability to survive under a wide range of environment conditions and to persist for long periods of time on areas represents a frequent cause of endemic infection hotbeds especially in the Intensive Care Unit.The objectives of the study are: determining the 5-year incidence of A. baumannii infection in patients admitted in the ICU which needed mechanical ventilation; the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 3 publications
2
10
0
1
Order By: Relevance
“…Our findings on resistance to the commonly prescribed cephalosporins are consistent with results from several previous studies in other parts of the world showing high resistance to third and fourth generation cephalosporins, for instance a survey in tertiary hospitals in Colombia, Turkey, Romania, and Sudan reported resistance to cefotaxime, ceftazidime, and cefepime with proportions ranging from 84% to 98% [21, 22, 27, 28]. In contrast, similar studies in the Netherlands and India reported resistance rate of 16%-56% to ceftazidime and cefepime [29, 30]. The high resistance to Beta-lactam antibiotics in Acinetobacter species especially A. baumannii is most likely associated with the production of B-lactamases including TEM-1 , TEM-2 and CARB-5, AR-1 , ACE-1, 2, 3, 4 and the ESBL whose genes are either chromosomally or plasmid located.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings on resistance to the commonly prescribed cephalosporins are consistent with results from several previous studies in other parts of the world showing high resistance to third and fourth generation cephalosporins, for instance a survey in tertiary hospitals in Colombia, Turkey, Romania, and Sudan reported resistance to cefotaxime, ceftazidime, and cefepime with proportions ranging from 84% to 98% [21, 22, 27, 28]. In contrast, similar studies in the Netherlands and India reported resistance rate of 16%-56% to ceftazidime and cefepime [29, 30]. The high resistance to Beta-lactam antibiotics in Acinetobacter species especially A. baumannii is most likely associated with the production of B-lactamases including TEM-1 , TEM-2 and CARB-5, AR-1 , ACE-1, 2, 3, 4 and the ESBL whose genes are either chromosomally or plasmid located.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings on resistance to the commonly prescribed cephalosporins namely ceftazidime and cefepime (36.1%-43.4%) are consistent with results from several previous studies in the Netherlands [18], USA [17] and India [19], which reported resistance rate of 16%-56% to ceftazidime and cefepime. Studies in Pakistan [20] have reported very high resistance to ceftazidime and cefepime (both 99.2%), which could be due to extensive use of antibiotics.…”
Section: Resultssupporting
confidence: 92%
“…This is likely due to the fact that colistin has been limited from being used during the last several decades due to nephrotoxicity. Now, colistin has been revaluated for treatment of MDR A. baumannii for its low resistance 33 . However, resistance to colistin is also emerging.…”
Section: Discussionmentioning
confidence: 99%